Ankle muscle strength and activation are associated with walking patterns in preschool and school-age children - Sudarat Apibantaweesakul; Shiho Omura; Weihuang Qi; Natsuki Sado; Hiroto Shiotani; Fumiko Tanaka; Plaiwan Suttanon; Yasuo Kawakami (PLoS ONE, 2025)
Walking patterns can differ between children and adults, both kinematically and kinetically. However, the detailed nature of the ankle pattern has not been clarified. We investigated musculature, biomechanics, and muscle activation strategies and their relevance to walking performance in preschool (PS) and school children (SC), with adults (AD) as reference. Twenty-six PS (3–5 yr), 20 SC (6–8 yr), and 17 AD (18–30 yr) participated. Tibialis anterior (TA) and medial gastrocnemius (MG) thicknesses, fascicle lengths, and maximal voluntary dorsi- and plantar flexion isometric torques were measured. Hip, knee, and ankle kinematics, ground reaction forces (GRFs), and TA and MG electromyographic activities were recorded during shod walking at each participant’s preferred speed. Walking speed, step length, and cadence were correlated with age in PS. These walking performance measures were also correlated with muscle thickness and fascicle length, showing higher speed in individuals with thicker muscles and longer TA and MG fascicles (conversely, higher cadence with thinner muscles and shorter fascicles). AD demonstrated the largest values for muscle thickness (p<0.001), fascicle length (p<0.001), strength (p<0.001), and walking performance (speed p = 0.004; step length p<0.001; cadence p<0.001), followed by SC then PS. Both PS and SC exhibited higher TA activities than AD during the stance phase, resulting in a higher co-activation index. The GRFs relative to body weight were lower in both horizontal and vertical components in PS compared to SC and AD, while the relative lateral force during stance was greatest in PS followed by SC and then AD. Differences in preferred walking speed and step length were associated with age and muscle size. Children, particularly preschool-aged, employed a co-activation strategy of dorsi- and plantar flexors for stabilization, which resulted in sideways steps even at a preferred walking speed.